Corrigendum to “On the use of 6C seismic station for bending-to-shear and torsional building response assessment at TAIPEI 101” [Eng Struct 361 (2026) 122782] - Yara Rossi; Philippe Guéguen; Felix Bernauer; Kate Huihsuan Chen; Chin-Jen Lin; Chin-Shang Ku; Yaochieh Chen (Engineering Structures, 2026)

On the use of 6C seismic station for bending-to-shear and torsional building response assessment at TAIPEI101 - Yara Rossi; Philippe Guéguen; Felix Bernauer; Kate Huihsuan Chen; Chin-Jen Lin; Chin-Shang Ku; Yaochieh Chen (Engineering Structures, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

What you eat affects how you mate: sex-specific plasticity in black soldier fly reproduction driven by larval nutrition - Qi-Hui Zhang; Keng Hee Ng; Wells Shijian Chin; Yong Jen Tang; Jielin Lin; Nalini Puniamoorthy (Animal Behaviour, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Copper nanoparticles encapsulated in reduced graphene oxide electrode (CuxrGO1-x) for the electrochemical quantification of metformin in water - Yu-Jen Shih; Yu-Qiao Su; Wei-Hsiang Chen; Sheng-Kai Lin; Yi-Chun He; Chin-Pao Huang (Chemical Engineering Journal, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Genetic variants of retinol-binding protein 4 in adolescents are associated with liver function and inflammatory markers but not with obesity and insulin resistance - CHIN-JUNG LIN; NAIN-FENG CHU; YI-JEN HUNG; DEE PEI; CHIEN-HSING LEE; FONE-CHING HSIAO; CHIEH-HUA LU; CHANG-HSUN HSIEH (Journal of Genetics, 2015)

The interplay of sediment characteristics, depth, water temperature, and ocean currents shaping the biogeography of lancelets ( S ubphylum C ephalochordata) in the NW P acific waters - Hsiu‐Chin Lin; Jen‐Ping Chen; Benny K K Chan; Kwang‐Tsao Shao (Marine Ecology, 2015)
Lancelets (or amphioxus) are often found within the soft bottom of shallow tropical and temperate seas. The present study is the first to provide a fine‐scale biogeography of five species of lancelets ( A symmetron lucayanum , B ranchiostoma belcheri , B ranchiostoma japonicum , E pigonichthys cultellus , and E pigonichthys maldivensis ) in the NW Pacific and examine the effects of multiple environmental parameters. From multivariate analyses, the distribution and abundance patterns of lancelets were explained by a combination of factors comprising depth, temperature of the collecting month, mean temperature of the coldest month in the year, medium particle size and silt/clay ratio of the sediments. In addition, ocean currents also affect their distribution range. The major occurrence of A . lucayanum and E . maldivensis was associated with the warm K uroshio current, but E . maldivensis exhibited higher tolerance to low salinity and low temperature, and preferred substrata of slightly larger grain size, a lower ratio of suspended sediments, and deeper water. The closely related B . belcheri and B . japonicum exhibited fine‐scale habitat differentiation, and B . japonicum was abundant along the southern coast of C hina, where the salinity is lower in winter because of the C hina Coastal Current and the substratum is composed of very coarse sand with suspended sediments. Branchiostoma belcheri occurred in low abundance and was only recorded in N orthern T aiwan and the T aiwan Banks. Epigonichthys cultellus was found only at the T aiwan Banks, which had deep water, coarse sand, and a negligible amount of suspended sediments.

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Investigation of array-derived rotation in TAIPEI 101 - Chin-Jen Lin; Wen-Gee Huang; Han-Pang Huang; Bor-Shouh Huang; Chin-Shang Ku; Chun-Chi Liu (Journal of Seismology, 2012)

Investigation of ground rotational motions caused by direct and scattered P-waves from the 4 March 2008 TAIGER explosion experiment - Nguyen Dinh Pham; Bor-Shouh Huang; Chin-Jen Lin; Tuan-Minh Vu; Ngoc-Anh Tran (Journal of Seismology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Plant regeneration through shoot formation from callus of Areca catechu L. - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Plant regeneration through somatic embryogenesis from zygotic embryo-derived callus of Areca catechu L. (Arecaceae) - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (In Vitro Cellular & Developmental Biology - Plant, 2003)